Cage Culture Turbidostat: a Device for Rapid Determination of Algal Growth Rate - Skipnes, Olav (1980)
The present cage culture turbidostat consists of a growth chamber and a control unit. The microorganisms (photoautotrophic algae) are kept in the growth chamber by porous membranes (pore size 1 to 3 μm) which retain the algae but allow efficient exchange of the growth medium. Flow rate and composition of the medium can therefore be varied independently of algal population density. A reciprocating pumping mode of the medium is introduced to obtain more gentle clearance of membranes than that provided by rotation or stirring in other membrane fermentors. Pulsed light and a light-emitting diode/light-sensitive transistor couple are used to monitor the turbidity of the culture, independent of external light needed for growth. The control unit keeps the turbidity constant by frequent activation of the dilution pump. Theoretical analysis of growth in the turbidostat shows that integrated activation time of the dilution pump is proportional to the growth rate of the organism. Theoretical analysis was also used to determine minimum flow-rate and nutrient concentration of medium to cover the requirement of the algae. Experiments with three different marine diatoms were carried out, and they demonstrated that the growth rate could be determined every hour and that the cultures could be kept at constant turbidity over 10 to 14 days at least.